2013
DOI: 10.1111/jphp.12033
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in P-glycoprotein at the blood–brain barrier in the early period of MCAO in rats

Abstract: P-gp plays a crucial role in limiting the entrance of agents into the brain after MCAO and the specific regulation of P-gp expression/activity may provide an important approach for the improvement of pharmacotherapy in ischaemic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 28 publications
1
40
0
2
Order By: Relevance
“…BBB P-gp expression and activity is elevated three hours following transient intraluminal middle cerebral artery occlusion (MCAO). The observed overexpression of P-gp was persistent up to 24 hours after reperfusion, independent of the severity of the ischaemic event and observed also in newly generated capillaries 14 days post-stroke (Cen et al, 2013; Dazert et al, 2006; Hermann et al, 2006; Ueno et al, 2009). In contrast only a few studies have investigated the role of other ABC efflux transporters at the BBB after brain ischaemia.…”
Section: Introductionmentioning
confidence: 73%
“…BBB P-gp expression and activity is elevated three hours following transient intraluminal middle cerebral artery occlusion (MCAO). The observed overexpression of P-gp was persistent up to 24 hours after reperfusion, independent of the severity of the ischaemic event and observed also in newly generated capillaries 14 days post-stroke (Cen et al, 2013; Dazert et al, 2006; Hermann et al, 2006; Ueno et al, 2009). In contrast only a few studies have investigated the role of other ABC efflux transporters at the BBB after brain ischaemia.…”
Section: Introductionmentioning
confidence: 73%
“…Cell lysate (80  μ g) was resolved on 4–12% SDS-PAGE gels and then transferred on to nitrocellulose membranes. The membranes were blocked with tris-buffered saline with 0.1% Tween 20 and 5% skim milk and then incubated with primary antibodies (1 : 100–1 : 5000) overnight at 4°C and then washed with TBST for three times and incubated with HRP-conjugated secondary antibody (1 : 2000) at room temperature for 1 h. Following three-time wash with TBST, the membranes were developed by the ECL detection kit [19]. The images of western blot were captured and analyzed by Bio-Rad imaging system.…”
Section: Methodsmentioning
confidence: 99%
“…Because of the narrow therapeutic window for the stroke, it is crucial to investigate the changes in P‐gp expression at the BBB in the early period of the disease. Our previous report showed that increased P‐gp expression at the BBB and decreased concentration of rhodamine 123 (Rh123) and nimodipine in the ischeamic brain tissues were observed within 6 h and 4 h after middle cerebral artery occlusion in rats, respectively, accompanied with elevated tumour necrosis factor‐α (TNF‐α) and nitric oxide synthase (NOS) expression in brain microvessels . Accordingly, to investigate which factors are involved in the changes in P‐gp in the rBMECs during ischaemia may provide assistance for the modulation of the efflux pump.…”
Section: Introductionmentioning
confidence: 99%